2017
DOI: 10.1039/c7qo00326a
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-catalyzed cascade annulation of alkynes with sodium arylsulfinates: assembly of 3-sulfenylcoumarin and 3-sulfenylquinolinone derivatives

Abstract: An efficient and environmentally benign iodine-catalyzed cascade cyclization has been achieved to afford functionalized 3-sulfenylcoumarin and 3-sulfenylquinolinone derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Recently, Jiang and co‐workers developed a versatile protocol to 3‐sulfenylcourmain and 3‐sulfenylquinolinone derivatives through iodine‐promoted cascade cyclization/sulfenylation of alkynes with sodium arylsulfinates (Scheme 3 a). [26a] Preliminary mechanistic studies indicated DMSO was essential in the reaction to recycle iodine. Meanwhile, disulfide was also applicable under standard conditions, which suggested that it might be the intermediate in this reaction.…”
Section: Iodine‐promoted C−s Bonds Formationmentioning
confidence: 99%
“…Recently, Jiang and co‐workers developed a versatile protocol to 3‐sulfenylcourmain and 3‐sulfenylquinolinone derivatives through iodine‐promoted cascade cyclization/sulfenylation of alkynes with sodium arylsulfinates (Scheme 3 a). [26a] Preliminary mechanistic studies indicated DMSO was essential in the reaction to recycle iodine. Meanwhile, disulfide was also applicable under standard conditions, which suggested that it might be the intermediate in this reaction.…”
Section: Iodine‐promoted C−s Bonds Formationmentioning
confidence: 99%
“…In 2017, Wu and co‐workers [242] reported iodine/P(Cy) 3 mediated electrophilic cyclization to afford 3‐sulfenylcoumarin or 3‐sulfenylquinolinones ( 385 , 386 ). The methodology was successfully applied by treating alkynoates or alkynamides scaffolds ( 86 , 384 ) with sodium sulfinates ( 49 ) in ionic liquid 1‐carboxymethyl‐3‐methylimidazolium tetrafluoroborate ([C 2 O 2 mim]BF 4 ).…”
Section: Sulfenylationmentioning
confidence: 99%
“…Finally, it was proposed that nucleophilic attack of enaminones on electrophile (RSI) (26 A) (generated in situ from heterocyclic thiones) resulted into sulfenylated enaminones (Scheme 127). [241] In 2017, Wu and co-workers [242] reported iodine/P(Cy differently substituted sodium aryl sulfinates were investigated. The reaction tolerated well sodium aryl sulfinates substituted with both electron donating and withdrawing substituents, and resulted into superior yields in case of electron donating groups.…”
Section: Iodine Mediated Sulfenylationmentioning
confidence: 99%
“…Wu, Jiang and co-workers 211 , ICl and TBAI were considered in a variety of solvents. After extensive screening, the optimal conditions were identified and used to explore the generality and scope of this reaction.…”
Section: Synthesis Of Oxygen-containing Heterocyclesmentioning
confidence: 99%